2019
DOI: 10.1016/j.foodhyd.2019.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant protein mixtures on the microstructure and rheological properties of myofibrillar protein gel derived from red sea bream (Pagrosomus major)

Abstract: Effect of plant protein mixtures on the microstructure and rheological properties of myofibrillar protein gel derived from red sea bream (Pagrosomus major), Food Hydrocolloids (2019), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(36 citation statements)
references
References 50 publications
2
33
1
Order By: Relevance
“…The addition of CPI also reduced the voids in the gel structure, which was consistent with the results of Jang et al 45 . One possible reason could be that, due to the gelation properties of CPI and MP, each protein can form its own structure after mixing and eventually they are intertwined to form a strong structure 4 . The CPI helps to improve the water‐binding ability of the MP gel during heating.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The addition of CPI also reduced the voids in the gel structure, which was consistent with the results of Jang et al 45 . One possible reason could be that, due to the gelation properties of CPI and MP, each protein can form its own structure after mixing and eventually they are intertwined to form a strong structure 4 . The CPI helps to improve the water‐binding ability of the MP gel during heating.…”
Section: Resultssupporting
confidence: 88%
“…The gel properties and rheological behavior of comminuted meat products would be affected by the functional properties of MP 3 . Lin et al 4 . found that the intake of plant‐based protein reduced the risk of obesity and coronary heart disease compared with animal‐based proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non‐meat or plant proteins have widely served as excellent candidates as fat or meat substitutes in the meat product processing industry and have been used to develop low‐fat and high‐protein meat products to meet the increasing demand of consumers (Sun & Arntfield, 2012). There are three main types of plant proteins: cereal proteins, oil‐seed proteins, and leguminous proteins (Lin et al., 2019). These non‐meat protein additives are generally incorporated to enhance the physical properties (e.g., texture‐related properties), flavor, nutrition, and cooking yield of meat products while reducing the cost of production (Sun & Arntfield, 2012).…”
Section: Modification Of Mpmentioning
confidence: 99%
“…Interestingly, the SDS‐PAGE results showed that some of the three non‐meat protein additives would be involved in MP gel formation to some extent. Among the different types of plant proteins applied in modifying the textural properties of MP gel and producing unique meat products, soy proteins (isolates or concentrates) are probably the most widely studied and used (Lin et al., 2019; Niu, Xia, Wang, Kong, & Liu, 2017; Sun & Arntfield, 2012; Sun & Holley, 2011). When using soy proteins as a functional ingredient in the comminuted and emulsified meats, the lack of structural changes for soy proteins during the interaction with MP molecules in the gel system under normal meat processing conditions (pH 5.5 to 6.0 and temperatures up to 75 °C) is probably the main obstacle hindering the formation of strong gels (Sun & Arntfield, 2012).…”
Section: Modification Of Mpmentioning
confidence: 99%